Relationship Between Lipodystrophy, Body Composition, Metabolic Profile, and Serum Levels of Adipocytokines - Sacilotto, Lívia Bertazzo [UNESP]; Papini, Silvia Justina [UNESP]; Mendes, Adriana Lucia [UNESP]; Gatto, Mariana [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; Corrente, José Eduardo [UNESP]; Silva, Julhiany de Fátima da [UNESP] (Frontiers, 2021)
Background: Despite the benefits in improving the clinical state of people living with HIV/aids (PLWHA), some side effects associated with the use of antiretroviral therapy (ART) are reported. Redistribution of body fat has been associated with treatment and is characterized by morphological changes, also known as lipodystrophy. The complications of metabolic and morphological changes in these individuals seem to increase the risk of cardiovascular disease. Adipocytokines are proteins that have essential functions in biological processes, in which the levels of these proteins are related to the pathogenesis of metabolic syndrome (MS) and cardiovascular disease. Recent studies have shown that such levels are generally modified in PLWHA, regardless of whether the treatment is established or not. An application of methods for body fat estimation in patients with fat redistribution, as in the case of aids, especially those that quantify body fat by segments, appears to clarify these alterations and plays an important role in the development of multiprofessional treatment. Objectives: This investigation was carried out to compare and correlate body composition, biochemical metabolic parameters, and levels of adipocytokines and cytokines of PLWHA, with and without lipodystrophy, with individuals with negative HIV serology and stratified by sex. Material and Methods: This is a cross-sectional study in which body composition, metabolic and anthropometric changes, and levels of adipocytokines of 110 individuals were assessed. These individuals were paired in sex, age, and body mass index (BMI) and subdivided into three groups: PLWHA with and without a clinical diagnosis of lipodystrophy associated with HIV, and a group control. Results: Collinearity was identified both in the general sample and for genders of the waist-to-height ratio (WHtR) with all anthropometric parameters, except for muscle mass. The results show strong association between IFN-γ and TNF-α both in the general sample and for genders and moderate correlation between leptin and fasting glucose for women; worsening of the triglyceride profile in both women with lipodystrophy compared with the control group and men without lipodystrophy compared with the control group; higher serum TNF-α values among men without lipodystrophy compared to those with HIV-associated lipodystrophy (HALS). Conclusions: The results of this study underline that, considering the manifestations of the syndrome, these patients have a high-risk endocrine metabolic profile for cardiovascular events.
Keywords: adipocytes; body composition; HIV; lipodystrophy; metabolic syndrome